Shedding light on rift formation in the southern Tibetan Plateau: insights from 3D magnetotelluric modeling - Zhehan Liu; Hao Dong; Sheng Jin; Wenbo Wei; Gaofeng Ye; Letian Zhang (Earth, Planets and Space)
Abstract The north–south trending rifts in the southern Tibetan Plateau provide an ideal natural laboratory for understanding the plateau's tectonic evolutionary processes. However, open questions remain regarding how the deep-seated geodynamic processes interact with the surface deformation. In this study, we conduct three-dimensional electrical modeling of the crust and upper mantle structure in the western Lhasa terrane. Our results reveal a contrasting distribution of high-conductivity anomalies beneath the Yare Rift (YRR), Lunggar Rift (LGR), and Nyalam–Coqen Rift (NCR). Conductive zones beneath the LGR and YRR extend laterally within the crust, while the anomalies beneath the north part of the NCR plunge deep into the mantle. These variations suggest that the mechanisms of rift formation may be different. To elucidate these mechanisms, we analyze the causes of the high-conductivity anomalies beneath the rifts. The anomalies beneath the LGR and YRR are attributed to saline fluids or silicate melts, while those beneath the NCR require a mixture of silicate and carbonate melts. The results suggest that the formation of the LGR and YRR is driven by the northward underthrusting of the Indian plate. This process promotes the migration of partial melts or fluids, which induce east–west extensional stress, resulting in rifting within the brittle upper crust. On the other hand, the formation of the NCR may result from a combined effect of the asthenospheric upwelling in the northern region and east–west extension of the weak middle crust to the south. Graphical Abstract